Process for increasing the content of silicon dioxide in lepidolite tailings
Patent Information
- Application Number
- CN202311517004.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-15
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-11-15
AI Technical Summary
[0003]现有技术对锂云母尾矿二氧化硅的回收需要经过脱泥、磨矿、磁选、浮选等工艺流程,在磨矿过程中和浮选过程中,由于矿浆的流动性差和捕收剂的选择性低,混合矿浆易发生泥化现象,从而形成矿泥罩盖,阻碍浮选过程矿物的上浮,影响二氧化硅与其他组分的分离效果,导致二氧化硅含量降低,同时也会增加药剂消耗,增加生产成本,因此,需要一种提高锂云母尾矿中二氧化硅含量的工艺,以解决现有问题
[0037]1. This invention uses sodium hexametaphosphate as a quartz depressant, which can prevent quartz particles from combining with the collector and floating, thereby reducing the loss of silica. At the same time, sodium hexametaphosphate and sodium carbonate are used as dispersants for the slurry, which can increase the negative surface potential of fine particles, prevent the agglomeration of fine mineral particles, increase the fluidity of the slurry, thereby improving the flotation effect and helping to remove other components by flotation, thus reducing the impurity content of quartz tailings.
Smart Images

Figure CN117619552B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of mineral recycling technology, specifically to a process for increasing the silica content in lepidolite tailings. Background Technology
[0002] Lepidolite is the most common lithium mineral and a raw material for lithium extraction. It is a basic aluminosilicate of potassium and lithium. After valuable concentrate is extracted from lepidolite ore in a beneficiation plant, the resulting waste is called lepidolite tailings. These tailings contain residual useful components such as silica, as well as harmful components in large quantities, which cannot be discharged arbitrarily. Therefore, it is necessary to recover the silica from the lepidolite tailings.
[0003] Existing technologies for recovering silica from lepidolite tailings require processes such as desliming, grinding, magnetic separation, and flotation. During grinding and flotation, due to the poor fluidity of the slurry and the low selectivity of the collector, the mixed slurry is prone to mud formation, resulting in a mud cover that hinders the floating of minerals during flotation, affects the separation of silica from other components, and leads to a decrease in silica content. It also increases reagent consumption and production costs. Therefore, a process is needed to increase the silica content in lepidolite tailings to solve the existing problems. Summary of the Invention
[0004] In view of the shortcomings of the prior art, the purpose of this invention is to provide a process for increasing the silica content in lepidolite tailings.
[0005] A process for increasing the silica content in lepidolite tailings specifically includes the following steps:
[0006] S1: Desliming and weak magnetic separation of lithium mica tailings
[0007] The lithium mica tailings are classified by cyclone grading, overflow desliming, and magnetic separation to obtain demagnetized coarse sand;
[0008] S2: Add magnetic starch for demagnetization and coarse sand flocculation treatment.
[0009] The demagnetized coarse sand was ball-milled, and a dispersant and magnetic starch were added for flocculation. After standing, the upper layer of solid and liquid was separated and dried to obtain demagnetized sand particles.
[0010] S3: Demagnetizing sand particles agitated and dissolved
[0011] Mix demagnetized sand particles with 1-1.5 parts by volume of deionized water, add 0.5-0.7 parts by mass of sodium hydroxide, and mechanically stir at high speed for 20-30 minutes to obtain a dissolving slurry;
[0012] S4: Add modified oleic acid for reverse flotation to reduce impurities.
[0013] The molten slurry, inhibitor, and modified oleic acid are mixed, ultrasonically treated, pH adjusted, reverse flotation performed, filtered, and dried to obtain intermediate tailings.
[0014] S5: Dual flotation separation
[0015] The intermediate tailings were subjected to lithium flotation separation and feldspar flotation separation to obtain quartz tailings.
[0016] Furthermore, step S1, the desliming and weak magnetic separation of the lithium mica tailings, specifically includes the following steps:
[0017] S1.1: Use a large-diameter hydrocyclone with a diameter of φ250-500mm to classify the lepidolite tailings, use a small-diameter hydrocyclone with a diameter of φ50-75mm to overflow and deslim the coarse part, and obtain coarse sand from the fine part of the tailings.
[0018] S1.2: Place the tailings coarse sand in a magnetic separator for weak magnetic separation to obtain demagnetized coarse sand and magnetite.
[0019] Further, step S2 involves adding magnetic starch for demagnetization and coarse sand flocculation treatment, specifically including the following steps:
[0020] S2.1: Weigh 500-700 parts by weight of demagnetized coarse sand, place it in a conical ball mill, add deionized water at a mass ratio of 1:(1-2), and ball mill until the fineness is -(0.074-0.094) mm to obtain raw ore slurry;
[0021] S2.2: Mix magnetic seeds with carboxymethyl starch in a ratio of (10-12):1, and grind them in a ball mill to obtain magnetic starch;
[0022] S2.3: Add 0.05-0.1% of dispersant and 0.075-0.1% of magnetic starch by total mass to the raw ore mortar, mix well, and let stand;
[0023] S2.4: The liquid stratification detector detects that the raw ore slurry has been completely stratified and sends a signal to the controller to open the bottom solenoid valve. The bottom flocculent is discharged into the collection chamber. The gravity sensor in the collection chamber detects that the gravity exceeds the set threshold and sends a signal to the controller to close the solenoid valve, thus obtaining the supernatant containing suspended minerals.
[0024] S2.5: The supernatant containing suspended minerals is subjected to solid-liquid separation and dried to obtain demagnetized sand particles.
[0025] Further, step S4 involves adding modified oleic acid for reverse flotation to reduce impurities, specifically including the following steps:
[0026] S4.1: Mix oleic acid and sodium hydroxide at an oil-alkali mass ratio of (17-20):1, add deionized water, and heat and stir in a water bath at 60-70℃ for 10-15 minutes to obtain modified oleic acid.
[0027] S4.2: Add 0.009-0.012 g / L inhibitor and 0.027-0.035 g / L modified oleic acid to the dissolving slurry, stir evenly, perform ultrasonic treatment, and let stand for 20-30 minutes to obtain a mixed slurry;
[0028] S4.3: Add alkaline reagent to adjust the pH of the mixed slurry to 7-8, stir in the flotation machine for 3-5 minutes, aerate, scrape the bubbles for 4-8 minutes, and carry out reverse flotation to obtain calcite froth and reverse flotation slurry;
[0029] S4.4: The reverse flotation slurry is filtered and dried in a drying oven at 50-60℃ to obtain intermediate tailings.
[0030] Furthermore, step S5, dual flotation separation, specifically includes the following steps:
[0031] S5.1: Place intermediate tailings one in a single-cell flotation machine, add collector BK414A at 0.05-0.075% of the total mass, stir and adjust the slurry, aerate, and perform flotation to separate lepidolite froth. Dewater the remaining slurry to obtain intermediate tailings two.
[0032] S5.2: Place the intermediate tailings 2 in a flotation machine, add collector BK435-1 accounting for 0.05-0.075% of the total mass, stir and adjust the slurry, then aerate and float to separate the feldspar froth. The remaining slurry is dewatered to obtain quartz tailings.
[0033] Furthermore, the magnetic seed used in step S2.2 is the magnetite obtained in step S1.2.
[0034] Furthermore, the dispersant in step S2.3 and the inhibitor in step S4.2 are both sodium hexametaphosphate, and the alkaline reagent in step S4.3 is sodium carbonate.
[0035] Further, the calcite foam from step S4.3, the lepidolite foam from step S5.1, and the feldspar foam from step S5.2 are dehydrated to obtain calcite concentrate, lepidolite concentrate, and feldspar concentrate.
[0036] The beneficial effects are:
[0037] 1. This invention uses sodium hexametaphosphate as a quartz depressant, which can prevent quartz particles from combining with the collector and floating, thereby reducing the loss of silica. At the same time, sodium hexametaphosphate and sodium carbonate are used as dispersants for the slurry, which can increase the negative surface potential of fine particles, prevent the agglomeration of fine mineral particles, increase the fluidity of the slurry, thereby improving the flotation effect and helping to remove other components by flotation, thus reducing the impurity content of quartz tailings.
[0038] 2. This invention utilizes a weak magnetic separation-magnetic starch flocculation method. By magnetizing carboxymethyl starch with magnetite obtained from weak magnetic separation, fine hematite particles are brought closer together and form quasi-stable magnetic agglomerates centered on the magnetic starch. This enhances the adsorption capacity of carboxymethyl starch for iron components, accelerates the flocculation rate, and increases the particle size of the flocculated particles to facilitate sedimentation, thereby achieving efficient iron removal while avoiding strong magnetic separation to save energy.
[0039] 3. By adding sodium hydroxide to adjust the alkaline environment, this invention can selectively dissolve the silicon components on the surface of mineral particles, thereby increasing the silica content in the tailings. High-speed stirring and scrubbing helps to expose the fresh surface of the mineral particles, thereby strengthening the interaction between the reagent and the mineral surface. At the same time, it changes the surface electrical properties and hydrophilicity / hydrophobicity of the mineral particles, which helps the silicon components to separate from other components.
[0040] 4. This invention uses sodium hydroxide to modify oleic acid, which can enhance the adsorption of calcite. By ultrasonically treating the slurry after adding modified oleic acid, the floatability of calcite can be improved, making it easier to remove calcite by reverse flotation.
[0041] 5. By using collector BK414A, this invention can improve the selectivity for lithium components. At the same time, collector BK414A has foaming properties, which is beneficial for cleaning the fine-grained sludge covering the mineral surface, reducing mud formation, promoting the adsorption of the collector on the surface of lepidolite, and helping to remove lithium by flotation.
[0042] 6. This invention uses a liquid stratification detector to detect the stratification of raw ore slurry. It can send a signal to the controller to open the solenoid valve, allowing the bottom iron component flocculent to be discharged. The amount of flocculent discharged is detected by a gravity sensor in the collection chamber, which enables the controller to automatically close the solenoid valve, thereby achieving automatic separation of the bottom flocculent and the upper suspended minerals. Attached Figure Description
[0043] Figure 1 This is a process flow diagram for increasing the silica content in lepidolite tailings, as used in an embodiment of the present invention. Detailed Implementation
[0044] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0045] Example 1
[0046] A process for increasing the silica content in lepidolite tailings, such as... Figure 1 As shown, the specific steps include:
[0047] S1: Desliming and weak magnetic separation of lithium mica tailings
[0048] The lithium mica tailings were classified using a φ300mm large-diameter hydrocyclone. The coarse particles were deslimed by overflow using a φ50mm small-diameter hydrocyclone, and the fine particles were used to obtain coarse sand from the tailings.
[0049] The tailings coarse sand is placed in a magnetic separator for weak magnetic separation to obtain demagnetized coarse sand and magnetite.
[0050] S2: Add magnetic starch for demagnetization and coarse sand flocculation treatment.
[0051] Weigh 500 parts by weight of demagnetized coarse sand, place it in a conical ball mill, add deionized water at a mass ratio of 1:1, and ball mill until the fineness is -0.074 mm to obtain raw ore slurry;
[0052] Magnetite and carboxymethyl starch were mixed in a 10:1 ratio and ground in a ball mill to obtain magnetic starch.
[0053] Add 0.05% of the total mass of dispersant and 0.075% of the total mass of magnetic starch to the raw ore mortar, mix well, and let stand;
[0054] The liquid stratification detector detects that the raw ore slurry has been completely stratified and sends a signal to the controller to open the bottom solenoid valve. The bottom flocculent is discharged into the collection chamber. The gravity sensor in the collection chamber detects that the gravity exceeds the set threshold and sends a signal to the controller to close the solenoid valve, thus obtaining the supernatant containing suspended minerals.
[0055] The supernatant containing suspended minerals is subjected to solid-liquid separation and dried to obtain demagnetized sand particles.
[0056] S3: Demagnetizing sand particles agitated and dissolved
[0057] Mix demagnetized sand particles with 1 volume part of deionized water, add 0.5 mass parts of sodium hydroxide, and mechanically stir at high speed for 20 minutes to obtain a dissolving slurry;
[0058] S4: Add modified oleic acid for reverse flotation to reduce impurities.
[0059] Oleic acid and sodium hydroxide were mixed at an oil-alkali mass ratio of 20:1, deionized water was added, and the mixture was heated and stirred in a 60°C water bath for 10 minutes to obtain modified oleic acid.
[0060] Add 0.009 g / L sodium hexametaphosphate and 0.027 g / L modified oleic acid to the slurry, stir evenly, perform ultrasonic treatment, and let stand for 20 minutes to obtain a mixed slurry;
[0061] Sodium carbonate was added to adjust the pH of the mixed slurry to 7. After stirring for 3 minutes in the flotation machine, the mixture was aerated and skimmed for 4 minutes. Then, reverse flotation was performed to obtain calcite froth and reverse flotation slurry.
[0062] The reverse flotation slurry was filtered and dried in a 50°C drying oven to obtain intermediate tailings.
[0063] S5: Dual flotation separation
[0064] The intermediate tailings 1 were placed in a single-cell flotation machine, and collector BK414A was added at 0.05% of the total mass. After stirring and adjusting the slurry, the mixture was aerated and subjected to flotation by scraping foam to separate the lepidolite foam. The remaining slurry was dewatered to obtain intermediate tailings 2.
[0065] The intermediate tailings were placed in a flotation machine, and collector BK435-1, accounting for 0.06% of the total mass, was added. After stirring and adjusting the slurry, the slurry was aerated and floated to separate the feldspar froth. The remaining slurry was dewatered to obtain quartz tailings.
[0066] Example 2
[0067] A process for increasing the silica content in lepidolite tailings, such as... Figure 1 As shown, the specific steps include:
[0068] S1: Desliming and weak magnetic separation of lithium mica tailings
[0069] The lithium mica tailings were classified using a φ300mm large-diameter hydrocyclone. The coarse particles were deslimed by overflow using a φ50mm small-diameter hydrocyclone, and the fine particles were used to obtain coarse sand from the tailings.
[0070] The tailings coarse sand is placed in a magnetic separator for weak magnetic separation to obtain demagnetized coarse sand and magnetite.
[0071] S2: Add magnetic starch for demagnetization and coarse sand flocculation treatment.
[0072] Weigh 500 parts by weight of demagnetized coarse sand, place it in a conical ball mill, add deionized water at a mass ratio of 1:2, and ball mill until the fineness is -0.074mm to obtain raw ore slurry;
[0073] Magnetite and carboxymethyl starch were mixed in a 12:1 ratio and ground in a ball mill to obtain magnetic starch.
[0074] Add 0.07% of the total mass of dispersant and 0.085% of the total mass of magnetic starch to the raw ore mortar, mix well, and let stand;
[0075] The liquid stratification detector detects that the raw ore slurry has been completely stratified and sends a signal to the controller to open the bottom solenoid valve. The bottom flocculent is discharged into the collection chamber. The gravity sensor in the collection chamber detects that the gravity exceeds the set threshold and sends a signal to the controller to close the solenoid valve, thus obtaining the supernatant containing suspended minerals.
[0076] The supernatant containing suspended minerals is subjected to solid-liquid separation and dried to obtain demagnetized sand particles.
[0077] S3: Demagnetizing sand particles agitated and dissolved
[0078] Mix demagnetized sand particles with 1.2 parts by volume of deionized water, add 0.7 parts by mass of sodium hydroxide, and mechanically stir at high speed for 20 minutes to obtain a dissolving slurry;
[0079] S4: Add modified oleic acid for reverse flotation to reduce impurities.
[0080] Oleic acid and sodium hydroxide were mixed at an oil-alkali mass ratio of 17:1, deionized water was added, and the mixture was heated and stirred in a 60°C water bath for 10 minutes to obtain modified oleic acid.
[0081] Add 0.012 g / L sodium hexametaphosphate and 0.035 g / L modified oleic acid to the slurry, stir evenly, perform ultrasonic treatment, and let stand for 20 minutes to obtain a mixed slurry;
[0082] Sodium carbonate was added to adjust the pH of the mixed slurry to 8. After stirring for 3 minutes in the flotation machine, the mixture was aerated and skimmed for 4 minutes. Then, reverse flotation was performed to obtain calcite froth and reverse flotation slurry.
[0083] The reverse flotation slurry was filtered and dried in a 50°C drying oven to obtain intermediate tailings.
[0084] S5: Dual flotation separation
[0085] The intermediate tailings 1 were placed in a single-cell flotation machine, and collector BK414A was added at 0.06% of the total mass. After stirring and adjusting the slurry, the mixture was aerated and subjected to flotation by scraping foam to separate the lepidolite foam. The remaining slurry was dewatered to obtain intermediate tailings 2.
[0086] The intermediate tailings were placed in a flotation machine, and collector BK435-1, accounting for 0.07% of the total mass, was added. After stirring and adjusting the slurry, the slurry was aerated and floated to separate the feldspar froth. The remaining slurry was dewatered to obtain quartz tailings.
[0087] Example 3
[0088] A process for increasing the silica content in lepidolite tailings, such as... Figure 1 As shown, the specific steps include:
[0089] S1: Desliming and weak magnetic separation of lithium mica tailings
[0090] The lithium mica tailings were classified using a φ400mm large-diameter hydrocyclone. The coarse particles were deslimed by overflow using a φ60mm small-diameter hydrocyclone, and the fine particles were used to obtain coarse sand from the tailings.
[0091] The tailings coarse sand is placed in a magnetic separator for weak magnetic separation to obtain demagnetized coarse sand and magnetite.
[0092] S2: Add magnetic starch for demagnetization and coarse sand flocculation treatment.
[0093] Weigh 500 parts by weight of demagnetized coarse sand, place it in a conical ball mill, add deionized water at a mass ratio of 1:1, and ball mill until the fineness is -0.084 mm to obtain raw ore slurry;
[0094] Magnetite and carboxymethyl starch were mixed in a 10:1 ratio and ground in a ball mill to obtain magnetic starch.
[0095] Add 0.05% of the total mass of dispersant and 0.075% of the total mass of magnetic starch to the raw ore mortar, mix well, and let stand;
[0096] The liquid stratification detector detects that the raw ore slurry has been completely stratified and sends a signal to the controller to open the bottom solenoid valve. The bottom flocculent is discharged into the collection chamber. The gravity sensor in the collection chamber detects that the gravity exceeds the set threshold and sends a signal to the controller to close the solenoid valve, thus obtaining the supernatant containing suspended minerals.
[0097] The supernatant containing suspended minerals is subjected to solid-liquid separation and dried to obtain demagnetized sand particles.
[0098] S3: Demagnetizing sand particles agitated and dissolved
[0099] Mix demagnetized sand particles with 1 volume part of deionized water, add 0.5 mass parts of sodium hydroxide, and mechanically stir at high speed for 30 minutes to obtain a dissolving slurry;
[0100] S4: Add modified oleic acid for reverse flotation to reduce impurities.
[0101] Oleic acid and sodium hydroxide were mixed at an oil-alkali mass ratio of 20:1, deionized water was added, and the mixture was heated and stirred in a 70°C water bath for 15 minutes to obtain modified oleic acid.
[0102] Add 0.009 g / L sodium hexametaphosphate and 0.027 g / L modified oleic acid to the slurry, stir evenly, perform ultrasonic treatment, and let stand for 20 minutes to obtain a mixed slurry;
[0103] Sodium carbonate was added to adjust the pH of the mixed slurry to 7. After stirring for 5 minutes in the flotation machine, the mixture was aerated and skimmed for 7 minutes. Then, reverse flotation was performed to obtain calcite froth and reverse flotation slurry.
[0104] The reverse flotation slurry was filtered and dried in a drying oven at 60°C to obtain intermediate tailings.
[0105] S5: Dual flotation separation
[0106] The intermediate tailings 1 were placed in a single-cell flotation machine, and collector BK414A was added at 0.05% of the total mass. After stirring and adjusting the slurry, the mixture was aerated and subjected to flotation by scraping foam to separate the lepidolite foam. The remaining slurry was dewatered to obtain intermediate tailings 2.
[0107] The intermediate tailings were placed in a flotation machine, and collector BK435-1, accounting for 0.05% of the total mass, was added. After stirring and adjusting the slurry, the slurry was aerated and floated to separate the feldspar froth. The remaining slurry was dewatered to obtain quartz tailings.
[0108] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.
Claims
1. A process for increasing the silica content in lepidolite tailings, characterized in that, Specifically, the following steps are included: S1: Desliming and weak magnetic separation of lithium mica tailings The lithium mica tailings are classified by cyclone grading, overflow desliming, and magnetic separation to obtain demagnetized coarse sand; S2: Add magnetic starch for demagnetization and coarse sand flocculation treatment. The demagnetized coarse sand was ball-milled, and a dispersant and magnetic starch were added for flocculation. After standing, the upper layer of solid and liquid was separated and dried to obtain demagnetized sand particles. S3: Demagnetizing sand particles agitated and dissolved Mix demagnetized sand particles with 1-1.5 parts by volume of deionized water, add 0.5-0.7 parts by mass of sodium hydroxide, and mechanically stir at high speed for 20-30 minutes to obtain a dissolving slurry; S4: Add modified oleic acid for reverse flotation to reduce impurities. The molten slurry, inhibitor, and modified oleic acid are mixed, ultrasonically treated, pH adjusted, reverse flotation performed, filtered, and dried to obtain intermediate tailings. S5: Dual flotation separation Lithium components were separated by flotation in the intermediate tailings, and feldspar was separated by flotation to obtain quartz tailings. Step S2 involves adding magnetic starch for demagnetization and coarse sand flocculation treatment, specifically including the following steps: S2.1: Weigh 500-700 parts by weight of demagnetized coarse sand, place it in a conical ball mill, add deionized water at a mass ratio of 1:(1-2), and ball mill until the fineness is -(0.074-0.094) mm to obtain raw ore slurry; S2.2: Mix magnetic seeds and carboxymethyl starch in a ratio of (10-12):1, and grind them in a ball mill to obtain magnetic starch; S2.3: Add 0.05-0.1% of dispersant and 0.075-0.1% of magnetic starch by total mass to the raw ore mortar, mix well, and let stand; S2.4: The liquid stratification detector detects that the raw ore slurry has been completely stratified and sends a signal to the controller to open the bottom solenoid valve. The bottom flocculent is discharged into the collection chamber. The gravity sensor in the collection chamber detects that the gravity exceeds the set threshold and sends a signal to the controller to close the solenoid valve, thus obtaining the supernatant containing suspended minerals. S2.5: The supernatant containing suspended minerals is subjected to solid-liquid separation and dried to obtain demagnetized sand particles.
2. The process for increasing the silica content in lepidolite tailings according to claim 1, characterized in that, Step S1, desliming and weak magnetic separation of lithium mica tailings, specifically includes the following steps: S1.1: Use a large-diameter hydrocyclone with a diameter of φ250-500mm to classify the lepidolite tailings, use a small-diameter hydrocyclone with a diameter of φ50-75mm to overflow and deslim the coarse part, and obtain coarse sand from the fine part of the tailings. S1.2: Place the tailings coarse sand in a magnetic separator for weak magnetic separation to obtain demagnetized coarse sand and magnetite.
3. The process for increasing the silica content in lepidolite tailings according to claim 1, characterized in that, Step S4 involves adding modified oleic acid for reverse flotation to reduce impurities, specifically including the following steps: S4.1: Mix oleic acid and sodium hydroxide at an oil-alkali mass ratio of (17-20):1, add deionized water, and heat and stir in a water bath at 60-70℃ for 10-15 minutes to obtain modified oleic acid. S4.2: Add 0.009-0.012 g / L inhibitor and 0.027-0.035 g / L modified oleic acid to the dissolving slurry, stir evenly, perform ultrasonic treatment, and let stand for 20-30 minutes to obtain a mixed slurry; S4.3: Add alkaline reagent to adjust the pH of the mixed slurry to 7-8, stir in the flotation machine for 3-5 minutes, aerate, scrape the bubbles for 4-8 minutes, and carry out reverse flotation to obtain calcite froth and reverse flotation slurry; S4.4: The reverse flotation slurry is filtered and dried in a drying oven at 50-60℃ to obtain intermediate tailings.
4. The process for increasing the silica content in lepidolite tailings according to claim 1, characterized in that, Step S5, dual flotation separation, specifically includes the following steps: S5.1: Place intermediate tailings one in a single-cell flotation machine, add collector BK414A at 0.05-0.075% of the total mass, stir and adjust the slurry, aerate, and perform flotation to separate lepidolite froth. Dewater the remaining slurry to obtain intermediate tailings two. S5.2: Place the intermediate tailings 2 in a flotation machine, add collector BK435-1 accounting for 0.05-0.075% of the total mass, stir and adjust the slurry, then aerate and float to separate the feldspar froth. The remaining slurry is dewatered to obtain quartz tailings.
5. The process for increasing the silica content in lepidolite tailings according to claim 1, characterized in that, The magnetic seed used in step S2.2 is the magnetite obtained in step S1.
2.
6. The process for increasing the silica content in lepidolite tailings according to claim 3, characterized in that, The dispersant in step S2.3 and the inhibitor in step S4.2 are both sodium hexametaphosphate, and the alkaline reagent in step S4.3 is sodium carbonate.
7. The process for increasing the silica content in lepidolite tailings according to claim 4, characterized in that, Take the calcite foam from step S4.3, the lepidolite foam from step S5.1, and the feldspar foam from step S5.2, and dehydrate them respectively to obtain calcite concentrate, lepidolite concentrate, and feldspar concentrate.
Citation Information
Patent Citations
Selective flocculation reverse flotation desilication process of collophanite containing primary slime
CN102009001A
Preparation method and application of magnetic starch beneficiation reagent
CN107008573A